The Use of YouTube in Improving English Vocabulary Mastery in Early Childhood: Systematic Literature Review - Tohamba, Citra Prasiska Puspita (Yayasan Indonesia Emerging Literacy Education, 2025)
This study conducts a systematic literature review (SLR) to examine the role of YouTube in enhancing English vocabulary acquisition among early childhood learners aged 3–8. Drawing upon 60 peer-reviewed articles published between 2015 to 2025, the review analyzes how YouTube functions as a digital learning tool, the strategies employed in classroom and home settings, and the challenges that accompany its integration. Findings reveal that YouTube provides multimodal, engaging, and contextual input that significantly supports vocabulary recognition, retention, and recall. Songs, animated stories, and interactive videos were found to increase children’s motivation, stimulate cognitive processing, and create enjoyable learning experiences. Moreover, the review highlights the importance of scaffolding by teachers and parents, whose mediation maximizes the effectiveness of YouTube by providing explanation, repetition, and guided practice. Despite its potential, several challenges remain, including risks of distraction, excessive screen time, inappropriate content, and unequal digital access.